Biological Factors Influencing the Acquisition of Arabic as a Foreign Language - Simamora, Mukmin Ridoan; Ritonga, Arip Rachman; Azizah, Mufidah Asri; Rismawati, Yanda; Hamdani, Muhammad (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to provide an in-depth examination of how biological factors, including brain development, cognitive capacity, neurological processes, and age-related maturity, influence the acquisition of Arabic as a foreign language. The research method used a literature review method, analyzing empirical studies, books, and relevant academic articles published between 2015 and 2025. The literature was systematically selected through Scopus, Google Scholar, and Crossref, following PRISMA guidelines, and analyzed using a thematic narrative approach. The research findings indicate that Arabic language acquisition is strongly influenced by the phenomenon of the critical period, which is the phase when language learning is most optimal before the age of 12, when neural plasticity is at its peak. Nevertheless, neurological studies have shown that the adult brain is still capable of acquiring Arabic through neuroplastic processes that allow the reorganization of neural networks and the activation of key linguistic areas. Furthermore, differences in cognitive capacity also help explain variations in vocabulary retention and grammatical competence among learners. His study emphasizes the importance of understanding biological factors, such as brain maturation, neurolinguistic processes, working memory capacity, and age differences, in Arabic language learning. Teachers need to adjust teaching methods and materials according to learners’ cognitive stages and age, using consistent language exposure and guided practice. Integrating these biological findings can enhance learning effectiveness and support the development of an adaptive curriculum.